Pengaruh Penerapan Pembelajaran Daring, Tingkat Pendidikan Orangtua Dan Kecerdasan Emosional Terhadap Hasil Belajar Komputer Akuntansi - Siti Fathimatuzzaro; Rochmawati Rochmawati (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
The success of humans in obtaining education can be supported from several aspects, because the measure of human quality is determined by the level of learning outcomes. This research was conducted with the aim of analyzing the effect of learning, parental education levels and intelligence on learning outcomes of accounting computers. This type of research is quantitative using a sample of Surabaya state university students in the accounting education program class 2018 with purposive sampling technique and collecting data through a questionnaire. The results of regression analysis, partial test (t test) on variables X1, X3 are greater than t table, respectively 2.127 and 3.657. Whereas for the variable X2 t count is smaller than t table which is equal to 0.570. Which means the variable application of online learning (X1), emotional intelligence (X3) has a positive effect on the learning variable (Y) so Ho is rejected, Ha is accepted. The parental education level variable (X2) has no effect on the learning outcome variable (Y) so Ho is accepted, Ha is rejected. Simultaneous test results (f test) showed a result of 37.877 with a significance of 0.000, so Ho is rejected, Ha which says there is a positive influence between the application of learning outcomes of learning computer accounting is accepted. The result of the coefficient of determination (R ^ 2) obtained 0.666 shows that all independent variables affect the variable by 66.6%, while the other 33.4% are obtained from other variables outside the research.